Correspondence between Professional Learning Expectations and Learning Opportunities in Financial Management Textbooks (2023)
RESUMEN: This research investigated the correspondence between a sample of Financial Management textbooks and professional learning expectations synthesized in the construct of Expectation of Use. To this end, a conceptual framework developed from research on professional practice was integrated with the theoretical perspective of commognition and the analysis of mathematics education textbooks. A qualitative content analysis was performed on the narrative and the end-of-chapter problems of the textbooks, which identified the experiences they can offer and their relationship with professional practice. It was evidenced that the narrative of the textbooks focuses on promoting the development of concepts, principles, and procedures of financial theory; the financial situations presented in the narrative and in the end-of-chapter problems are artificial and therefore have limited relation with professional practice. It was concluded that, according to the textbooks, the mastery of Financial Management consists of appropriating a broad set of financial concepts that excludes the use of these concepts to address problems that simulate the profession. Restructuring the narrative in Financial Management textbooks and consciously including routines that respond to the professional learning needs of the financial community is recommended.